Analisis Pengaruh Manajemen Rekod dan Manajemen Risiko Terhadap Bisnis Proses Perusahaan Menggunakan Metode Structural Equation Modeling (SEM) - Puspitasari, Vina; Jannah, Miftahul (UI Scholars Hub, 2021)
The Implementation of record management through Electronic Document and Records Management System (EDRMS) that functions to provide systematic and computerized information that can be used to identify risks. EDRMS is part of the Business Information System (BIS) that required to carry out business activity to provide efficiency for data retrieval or decision making to support business process running well, minimize the occurrence of risks, and estimate the risks that will be faced. The purpose of this study to analyze the effect of record management, especially EDRMS, through its use and function positively related to risk management in company business process. The research method used was quantitative method by distribution questionnaires the processed using the Structural Equation Modeling (SEM) method based on Variance Partial Least Square (PLS) version 3.3.3. The results of this study showed that positive and significant effect between the uses of EDRMS as an information tool which is an important factor that related with decision making to determine the risks that will faced and how to deal with them. The effect of record management and risk management based on analysis test is 71, 5% on the company’s business processes.